CELEBRITY WORSHIP AS A MANIFESTATION OF ḤAMIYYAH JĀHILIYYAH IN THE POST-TRUTH ERA DOUBLE MOVEMENT ANALYSIS OF QS. AL-FATH 48: 26 - 'Afifah, Farida Nur; Hadi al-Asy'ari, M Khoirul (Al-Munir: Jurnal Studi Ilmu Al-Qur'an dan Tafsir, 2025)
Associated with a person's psychological state. Unwittingly, Celebrity Worship has become one of the manifestations of Hamiyyah Jahiliyyah in today's era, especially the post-truth era. This attitude is a threat to oneself because it is not by Islamic teachings. Individual fanaticism towards a person or group causes the truth to become unclear and forms a character that always feels the most in everything as explained in QS. Al-Fath [48]: 26. This article is a literature study analyzed with Fazlur Rahman's double movement theory to find out how the phenomenon of Celebrity Worship is viewed from the perspective of the Qur'an and how the correlation between Celebrity Worship and Hamiyyah Jahiliyyah. Likewise to see the cause and effect and how to avoid the attitude of Celebrity Worship. This study found that there is a correlation between the attitude of Celebrity Worship and Hamiyyah Jahiliyyah in terms of the characteristics that appear such as fanaticism to the level of worship, arrogance, and feeling the most in everything. Some things that influence the emergence of Celebrity Worship are age, education, social skills, and gender. The peak effect of this attitude is shirk because of the worship of individuals or groups so that they forget things related to divinity, especially in the post-truth era where the truth is unclear.